Short-term Montreal Cognitive Assessment predicts functional outcome after endovascular therapy - Zhang, Meng; Wang, Kun; Xie, Linlin; Pan, Xudong (Frontiers in Aging Neuroscience, 2022)
Background: Previous studies have shown that cognition in patients 4-8 weeks after stroke can predict early functional outcomes after stroke. The analyses of data from the REVASCAT trial proved that stent thrombectomy improves post-morbid wiring test outcomes in patients with AIS compared with drug therapy. However, few studies focus on the relationship between cognitive impairment and functional outcomes in patients undergoing endovascular treatment. Methods: 647 participants registered from stroke centers. Stroke severity was evaluated by NIHSS. The functional status was estimated by mRS. Cognitive impairment was assessed by trained neurologists at 14 ( ± 4)and 90 ( ±7)days after stroke onset using the Montreal Cognitive Assessment (MoCA). A MoCA score of less than 26 was considered post-stroke cognitive impairment(PSCI). Results: 120 Patients who underwent endovascular therapy were included. The PSCI group had higher levels of age, men, educational status, atrial fibrillation, smoking, alcoholism, ASPECT score of the anterior circulation, and OTP time than the non-PSCI group (P < 0.05). In contrast, the 14-day MoCA score, 14-day NIHSS score, 3-month MoCA score, 3-month NIHSS score, 3-month mRS score, and 3-month EQ5D score were lower in those PSCI patients. The risk predictors of PSCI were age, sex, educational level, atrial fibrillation, smoking, alcoholism, ASPECT Score(anterior circulation), 14-day MoCA score, and 14-day NIHSS score. There were strong relationships between 3-month NIHSS and MoCA(r=-0.483，p<0.001). ROC curve indicated that 14-day MoCA score, memory, abstraction, visuospatial/executive functions, attention, and languge, played a significant role to predict PSCI (AUC>0.7). It had predictive value for the 14-day visuospatial/executive functions to predict 3-month functional outcomes. Conclusion: Early application of the MoCA in different cognitive regions could predict the PSCI and future functional outcomes, which is necessary to screen high-risk patients with poor prognosis and conduct an early intervention.